Geometry of non-holonomic complexes NGr (1, 4, 4) in a four-dimensional affine space - Kazimieras Navickis (Lietuvos Matematikos Rinkinys)
In this article intrinsic normalizations of a non-holonomic complexes in affine space A4 is constructed in an invariant form.